THE EDUCATIONAL VALUES OF THE CHARACTER OF NOVEL’S SI ANAK KUAT BY TERE LIYE AND ITS IMPLICATIONS AS ALTERNATIVE TEACHING MATERIALS FOR LITERATURE LEARNING IN SENIOR HIGH SCHOOL - Yolanda, Putu Debby; Fuad, Muhammad; Munaris, Munaris (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2022)
This study aims to describe the educational values of the character of Tere Liye's novel Si Anak Kuat and its implications as teaching materials for literary learning in high school. The method used in this research is descriptive qualitative. The data source of this research is the novel Si Anak Kuat by Tere Liye. The data analysis technique used is the text content analysis technique. The results showed that the novel Si Anak Kuat by Tere Liye contained character education values which were analyzed based on the Ministry of Education and Culture's decree regarding the value of character education and Sigmund Freud's personality theory. The values of character education include five values, namely religious values, nationalism, independence, mutual cooperation, and integrity. The results of this study are implied into alternative teaching materials for learning literature in high school. The character education values found in this study can be used as a strengthening of character education in indirect learning.Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai pendidikan karakter novel Si Anak Kuat karya Tere Liye dan implikasinya sebagai bahan ajar pada pembelajaran sastra di SMA. Metode yang digunakan dalam penelitian ini ialah deskriptif kualitatif. Sumber data penelitian ini ialah novel Si Anak Kuat karya Tere Liye. Teknik analisis data yang digunakan adalah teknik analisis isi teks. Hasil penelitian menunjukkan bahwa novel Si Anak Kuat ini mengandung nilai-nilai pendidikan karakter yang dianalisis berdasarkan ketetapan Kemendikbud 2017 tentang nilai pendidikan karakter dan teori kepribadian Sigmund Freud. Nilai pendidikan karakter tersebut meliputi lima nilai,  yakni nilai religius, nasionalisme, kemandirian, gotong royong, dan integritas. Hasil penelitian ini diimplikasikan ke dalam alternatif bahan ajar pembelajaran sastra di SMA. Nilai-nilai pendidikan karakter yang ditemukan dalam penelitian ini dapat dimanfaatkan sebagai penguatan pendidikan karakter dalam pembelajaran tidak langsung.Keywords: The value of character education, the novel Si Anak Kuat, implications.